Aspergerʼs children: The origins of autism in Nazi Vienna - Sheffer, Edith (W.W. Norton et Company, 2018)
Chapter 1. Enter the experts – Chapter 2. The clinic's diagnosis – Chapter 3. Nazi psychiatry et social spirit – Chapter 4. Indexing lives – Chapter 5. Fatal theories – Chapter 6. Asperger et the killing system – Chapter 7. Girls et boys – Chapter 8. The daily life of death – Chapter 9. In service to the volk – Chapter 10. Reckoning.